The covid-19 detection with contactless method based on deep learning - Ismail, undefined; Fibriyanti, ,; Aidha, Zass Ressy; Menhendry, ,; Kamarul Hawari, Ghazali (Institute of Electrical and Electronics Engineers Inc., 2020)
The spread of corona virus diseases among medical workers is a big problem in this pandemic corona virus. The are many medical workers suffer and some of them died. The infected medical workers of corona virus are caused through directed or closed contacts between infected patients and medical workers. The closed and directed contact in medical services take place especially in diagnostic process. In order to handle this problem, the proposed method prevents the closed or directed contacts of medical workers to the suspected patients. The method uses RMI images or chest X-ray images data to predict the infected suspects. The proposed method is detecting the infected lung X-Ray image through Deep Learning model. It uses pre-trained model of GoogleNet, with modification. The Confusion Matrix and ROC curve are used to measure accuracy the predicted. They show that proposed method has high accuracy . Finally, the proposed method is able to replace closed or directed contact diagnostic done by medical workers to Covid-19 suspects. It has ability to handle the spread of Covid-19 among medical workers.